Detection of haemagglutinin D222 polymorphisms in influenza A(H1N1)pdm09‐infected patients by ultra‐deep pyrosequencing. (3rd August 2012) - Selleri, M.; Piralla, A.; Rozera, G.; Giombini, E.; Bartolini, B.; Abbate, I.; Campanini, G.; Rovida, F.; Dossena, L.; Capobianchi, M. R.; Baldanti, F.
Abstract This study was aimed at establishing the genetic heterogeneity of influenza virus haemagglutinin (HA) gene quasi‐species and the polymorphisms at codon 222, by application of ultra‐deep pyrosequencing (UDPS) to respiratory samples from patients hospitalized for influenza A(H1N1)pdm09 infection, presenting with severe or moderate–mild disease. HA diversity was significantly higher in samples collected from patients with severe manifestations than in those from patients with moderate–mild manifestations (p 0.02). D222 polymorphism was detected in 40.7% of patients by UDPS, and in only 7.1% by Sanger sequencing. D222E, D222G, D222N and D222A were observed in 37.0%, 11.1%, 7.4% and 3.7% of patients, respectively; 10.7% of samples harboured more than two variants. The relative frequency of each single variant showed a wide range of intrapatient variation. D222G/N/A were detected, as either minor or predominant variants, only in severe cases, whereas D222E was equally represented in severe and moderate–mild infections. Other amino acid variants were observed at different positions within the analysed HA fragment. Consistent with higher heterogeneity, non‐D222 variants were more frequently detected in severe cases than in moderate–mild cases. In addition, seven non‐D222 mutations carried by minority variants, not previously described, were observed.